2022
DOI: 10.1016/j.trim.2022.101549
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of procalcitonin (PCT) as a marker of infection in early post living donated liver transplant period

Abstract: Background: Procalcitonin (PCT) has been increasingly used as a biomarker of bacterial infection and as a tool to guide antimicrobial therapy. Despite its increased use, data in patients with solid organ transplants are limited.The study aim is to assess the frequency of rising procalcitonin associated with infectious complications in immunosuppressed living donated liver transplantation.Methods: A single center, retrospective observational study. Preoperative patients' demographic data, operative, anesthetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We reviewed 15 research papers with a total of 3,484 postoperative patients. Out of these finalized studies, two were systematic reviews and meta-analyses [21,22], two were narrative reviews [23,24], one was a nonrandomized clinical trial, and the remaining nine were observational studies [10][11][12][13][14][15][16][17][18][19], and one nonrandomized interventional study [20]. All studies involved operated patients and the measurement of CRP and PCT postoperatively during their in-hospital/ICU stay and their role in patients developing sepsis and SIRS.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed 15 research papers with a total of 3,484 postoperative patients. Out of these finalized studies, two were systematic reviews and meta-analyses [21,22], two were narrative reviews [23,24], one was a nonrandomized clinical trial, and the remaining nine were observational studies [10][11][12][13][14][15][16][17][18][19], and one nonrandomized interventional study [20]. All studies involved operated patients and the measurement of CRP and PCT postoperatively during their in-hospital/ICU stay and their role in patients developing sepsis and SIRS.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Table 4 shows the number of participants and the identified variables from the finalized studies. A retrospective observational study involving 60 postoperative liver transplant patients admitted to the ICU was conducted to determine the association between increased levels of PCT and infection and related complications in immunosuppressed patients [11]. They also explored non-infectious causes of the transplant.…”
Section: Role Of Procalcitonin In Managing Sepsis In Postoperative Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Although most studies excluded immunocompromised patients, 19 several studies have shown that the performance of procalcitonin is not compromised in SOT recipients, and that it may serve as a useful adjunct in ruling out bacterial infections in this population, thus avoiding unnecessary antibiotic use. 20,21 Allergy testing in patients with reported antibiotic allergies is a recommended stewardship activity. 2 In a study by Khumra et al, antibiotic allergies, particularly to sulfonamides and beta-lactams, were commonly reported in liver transplant recipients (16%).…”
Section: Discussionmentioning
confidence: 99%